Impact of pharmacologic therapy for benign prostatic hyperplasia on prostate volume and free testosterone and consequently on urinary parameters and sexual desire in men - Stojanović Nebojša; Đenić Nebojša; Bogdanović Dragan; Lazarević Konstansa (Vojnosanitetski Pregled)
Background/Aim. Pharmacologic therapy for benign prostatic hyperplasia (BPH) relieves disease progression and affects the androgen hormone status. A decrease in the level of free testosterone (freeT) within total testosterone (totalT) leads to symptoms of sexual dysfunction. The aim of this study was to show the impact of pharmacological treatment for BPH on prostate volume (PV) and levels of freeT and, consequently, on urinary parameters and sexual desire in men during 6 months of administration. Methods. This clinical prospective study included 156 BPH patients with moderate urinary symptoms – International Prostate Symptom Score (IPSS) < 19, PV > 30 mL and prostate specific antigen (PSA) value < 4 ng/mL. The average age of patients was 61.16 ± 2.97 years. The performed tests included determination of tumor markers (PSA, free PSA), hormones (totalT, freeT, freeT/totalT ratio), trans abdominal ultrasonography and uroflowmetry. Urinary symptoms were measured by IPSS and the Quality of Life (QoL) questionnaire while the changes in sexual desire were measured using the International Index of Erectile Function (IIEF) questionnaire. Four groups were formed, 39 patients each. The group 1 received alpha1- blocker (AB) tamsulosin, the group 2, 5 alpha-reductase inhibitor (5-ARI) finasteride, the group 3, combined therapy of both drugs (tamsulosin and finasteride), while the group 4 (control group) had no therapy. Follow-ups were performed every three and six months during therapy administration. Results. Prostate volume significantly decreased in the patients on combined therapy (-6.95 ± 2.00; p < 0.001) and finasteride (-6.67 ± 3.35). In the finasteride group, the levels of freeT (-4.23 ± 5.2; p < 0.001) and freeT/totalT ratio (-0.12 0.08; p < 0.001) significantly decreased as did the freeT (-2.64 ± 7.81) and freeT/totalT ratio (-0.09 ± 0.13) in the combined therapy group. Uroflowmetry showed a significant improvement in all parameters and all the therapy groups. Combined therapy provided the greatest improvement in the maximum flow rate (Qmax) (+4.06 ± 1.75; p < 0.001) and urinary symptoms (-10.95 ± 3.19). A significant improvement of sexual desire occurred in the patients on tamsulosin (+0.78 ± 1.00; p < 0.001), with a slight deterioration in the finasteride group, but without statistical significance. Conclusion. Hormonal component of pharmacologic therapy for BPH most effectively reduces PV and freeT levels, improves urinary symptoms with a slight decline of sexual desire in men on finasteride monotherapy.